A REVIEW OF NANOCELLULOSE SYNTHESIS METHODS AND ITS APPLICATION - Joko Waluyo (BRIN - Badan Riset dan Inovasi Nasional, 2023)
Nanocellulose is a type of cellulose that is being widely developed to replace petroleum-based polymers. This material possesses biocompatible properties, is abundant in nature, and is eco-friendly due to its biodegradability, sustainability, and non-toxic nature. Various nanocellulose synthesis methods are employed, including acid hydrolysis, alkaline, mechanical and biological treatments, as well as ionic liquid and deep eutectic solvent methods. The choice of synthesis method greatly influences the particle size and crystallinity of the resulting nanocellulose; hence further investigation is needed to determine the effectiveness of these methods. Nanocellulose finds applications in various fields, such as films, polymers, cosmetics, medical fuels, and energy storage. Among the different nanocellulose synthesis methods, ionic liquid and deep eutectic solvent (DES) methods have environmentally safe waste with better temperature, time, and diameter control compared to other methods. However, the DES method is currently preferred over the ionic liquid method due to the possibility of separating the lignin waste from the solvent.